Expression of genes responsible for cell morphogenesis involved in differentiation in porcine buccal pouch mucosal cells during long-term primary culture and real-time proliferation in vitro - Dyszkiewicz-Konwińska, M; Bryja, A; Jopek, K; Budna, J; Khozmi, R; Jeseta, M; Bukowska, D; Antosik, P; Bruska, M; Nowicki, M; Zabel, M; Kempisty, B (Journal of Biological Regulators & Homeostatic Agents, 2017)
Recently, using experimental animal model, we demonstrated that porcine buccal pouch mucosal cells reflect increased proliferation capability during primary cultivation in vitro. Although the histological structure and morphogenesis in oral cavity is well recognized, the molecular mechanisms which regulate this process still need further investigation. This study was aimed to analyze the molecular marker expression profile involved in morphogenesis and differentiation capacity of porcine buccal pouch mucosal cells during their long-term primary cultivation in vitro. The experiment was performed on buccal pouch mucosal cells isolated from 80 pubertal crossbred Landrace gilts. After collection, the cells were treated enzymatically and transferred into a primary in vitro culture (IVC) system and cultured for 30 days. The cells were collected for RNA isolation after 7, 15 and 30 days of IVC and were checked for their real-time proliferative status using the RTCA system. We found an increased expression of FN1 and SOX9 genes when calculated against ACTB after 7, and 30 days of IVC, (P less than 0.01, P less than 0.001, respectively). The CXCL12 mRNA was down-regulated after 7, 15 and 30 days of IVC, but not statistically significant. Similar expression profile was observed when calculated against HPRT, however, DAB2 was found to be higher expressed at day 15 of IVC, (P less than 0.05). The cell index measured during real-time cell proliferation was substantially increased between 96 h and 147h of IVC and reached the log phase. Since FN1 and SOX9 revealed significant increase of expression after long-term culture in vitro, it is suggested that expression of these differentiation and stemness genes is accompanied by cell proliferation. Moreover, FN1 and SOX9 might be recognized as new markers of buccal pouch mucosal cell proliferation and differentiation in pigs in in vitro primary culture model.
Keywords: vývojová regulace genové exprese; morfogeneze; RNA, Messenger; Mouth Mucosa; Hypoxanthine Phosphoribosyltransferase; ústní sliznice; zvířata; messenger RNA; Gene Expression Profiling; lipokalin-2; ženské pohlaví; buněčná diferenciace; SOX9 Transcription Factor; Cell Differentiation; Signal Transduction; proliferace buněk; Female; Primary Cell Culture; signální transdukce; transkripční faktor SOX9; Cell Proliferation; Epithelial Cells; Lipocalin-2; Morphogenesis; stanovení celkové genové exprese; Tumor Suppressor Proteins; hypoxanthinfosforibosyltransferasa; Swine; epitelové buňky; nádorové supresorové proteiny; Animals; prasata; Gene Expression Regulation, Developmental; primární buněčná kultura; chemokin CXCL12; Chemokine CXCL12